If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -1(2x + 1) = 7 + -1(x + -4) Reorder the terms: 7x + -1(1 + 2x) = 7 + -1(x + -4) 7x + (1 * -1 + 2x * -1) = 7 + -1(x + -4) 7x + (-1 + -2x) = 7 + -1(x + -4) Reorder the terms: -1 + 7x + -2x = 7 + -1(x + -4) Combine like terms: 7x + -2x = 5x -1 + 5x = 7 + -1(x + -4) Reorder the terms: -1 + 5x = 7 + -1(-4 + x) -1 + 5x = 7 + (-4 * -1 + x * -1) -1 + 5x = 7 + (4 + -1x) Combine like terms: 7 + 4 = 11 -1 + 5x = 11 + -1x Solving -1 + 5x = 11 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -1 + 5x + x = 11 + -1x + x Combine like terms: 5x + x = 6x -1 + 6x = 11 + -1x + x Combine like terms: -1x + x = 0 -1 + 6x = 11 + 0 -1 + 6x = 11 Add '1' to each side of the equation. -1 + 1 + 6x = 11 + 1 Combine like terms: -1 + 1 = 0 0 + 6x = 11 + 1 6x = 11 + 1 Combine like terms: 11 + 1 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 7s=21s-350 | | -18+16= | | 3*x+1=40 | | 3+1/2x=-4 | | 12/5w=13/10 | | r/-5-3=-14 | | -y^2+3y=9y+9 | | -3(2x+8)+6x= | | B-a/x | | 7y+9=Yt-6 | | h-18= | | -7(w-4)+3w-27=0 | | 16v^2+17v-45=0 | | 3w+4-w=5w+7-m | | 5m+4=4m | | -5(w-9)+8w+2= | | 2x^2-16x+29=0 | | -4x-7=-43 | | -6x-2=x-23 | | 5.3x+2=12.7-2 | | 7x/10=5 | | 3x-2/7=5/6 | | 6x-40=45 | | -6(4p+3)-49=5(2p+7) | | 4x^2=-24-20x | | 4.2x+31.5=-65.1 | | -86=4+10x | | 3.9x-13=1.7x+31 | | w^2+4w-124=0 | | 5/9(k-273.15) | | p=9+1.5(3) | | d/4-5 |